INTRAOPERATIVE LOCAL BUPIVACAINE WOUND INFILTRATION VERSUS TRADITIONAL SYSTEMATIC ANALGESIA: A COMPARISON IN TERM OF POST-OPERATIVE PAIN - AHMAD , A; ARIF , A; ATAULLAH , A; MUHAMMAD , F; KHAN , MA (Biological and Clinical Sciences Research Journal, 2024)
Effective management of post-operative pain is essential for patient recovery and satisfaction, especially in procedures like appendectomies where pain management can influence overall outcomes. Traditional systemic analgesia, while effective, often comes with side effects and limitations. Local infiltration of anesthetics like bupivacaine may provide a targeted approach to pain control with fewer systemic effects. Objective: To compare the effectiveness of intraoperative local bupivacaine wound infiltration versus traditional systemic analgesia in managing post-operative pain in patients undergoing appendectomies. Methods: This randomized controlled trial was conducted at Lady Reading Hospital, Peshawar, following approval from the hospital's Ethical Committee. A total of 60 patients, who consented and met eligibility criteria, were enrolled. All patients underwent appendectomy under general anesthesia, followed by random allocation into two groups. Group A received 0.5% bupivacaine for local wound infiltration, while Group B did not. Both groups were administered intravenous tramadol on demand, with a maximum dose of 400 mg per 24 hours. Post-operative pain was assessed using a Visual Analog Scale (VAS) at 4, 12, and 24 hours post-surgery. Stratified analysis by age and gender was also performed. Results: The study population (mean age: 41.13 ± 7.96 years) included 34 males (56.7%) and 26 females (43.3%). Group A (bupivacaine group) had a significantly lower mean post-operative pain score (3.33 ± 0.66) compared to Group B (systemic analgesia group) with a score of 5.30 ± 0.95 (p=0.00). Age-based stratification revealed significant differences: among 22-30-year-olds, Group A scored 3.00 versus 6.00 in Group B (p=0.00); for 31-50-year-olds, Group A scored 3.36 compared to 5.33 in Group B (p=0.00); and for those over 50, scores were 3.33 in Group A and 4.50 in Group B (p=0.04). Both male and female patients in Group A experienced significantly lower pain scores compared to Group B (p=0.00 for both). Conclusion: Intraoperative bupivacaine wound infiltration significantly reduces post-operative pain in appendectomy patients compared to traditional systemic analgesia. These findings support its use as an effective pain control method. Further research is recommended to optimize dosing and assess the combined use with other analgesics to enhance pain management across various surgical procedures.